2021
DOI: 10.1002/pc.26008
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of activated carbon/ultra‐high molecular weight polyethylene composites

Abstract: This research uses physical mixing and twin‐screw extrusion process to prepare biomass activated carbon (BAC)/ultra‐high molecular weight polyethylene (UHMWPE) composite materials. The mechanical properties, micro‐morphology, and thermodynamic properties of the composite materials were explored. The experimental results show that the tensile strength of 65% activated carbon added to the composite material has changed from 22.93 to 97.65 MPa, which is an increase of 325.86%. According to the Scanning electron m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…The practical enhancement in mechanical characteristics by incorporating nano activated carbon was perceived by Minugu, et al [ 23 ] in their studies. Wang et al [ 24 ] have investigated potential of activated carbon for enhancement of mechanical properties of ultra‐high molecular weight polyethylene composite materials. It was postulated that mechanical properties were significantly enhancement, an increment of 325.86% was observed for tensile strength.…”
Section: Introductionmentioning
confidence: 99%
“…The practical enhancement in mechanical characteristics by incorporating nano activated carbon was perceived by Minugu, et al [ 23 ] in their studies. Wang et al [ 24 ] have investigated potential of activated carbon for enhancement of mechanical properties of ultra‐high molecular weight polyethylene composite materials. It was postulated that mechanical properties were significantly enhancement, an increment of 325.86% was observed for tensile strength.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been conducted on the evaluation of the mechanical properties of AC/polymer composites; the results of some studies are summarized in Table 2 . Wang et al [ 77 ] reported the manufacturing method and analyzed the mechanical properties of biomass-activated carbon (BAC)/ultra-high-molecular-weight polyethylene (UHMWPE) composites using physical mixing and the twin-screw extrusion process. The results indicated that when 65% of BAC was added, the tensile strength increased by approximately 325.86%, from 22.93 to 97.65 MPa.…”
Section: Mechanical Properties Of Activated Carbon/polymer Compositesmentioning
confidence: 99%
“…For example, due to the porous structure, the molten polymer enters the pores of the activated carbon to form a three-dimensional network to improve the tensile properties of the composite material, or to improve the electrical properties or electromagnetic wave shielding properties of the polymer composite material due to its electrical conductivity. Owing to its low cost, excellent stability, and antistatic and electromagnetic interference shielding functions, AC/polymer composite material can be used in various applications, such as automobile parts and shielding materials [ 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among the various methods to reduce plastic waste colonization, the biodegradation technology is known to be the most accepted and eco-friendly method. The bioremediation method proceeds due to the potential microorganism action and without using any kind of heat [10]. Based on the oxygen utilization in the biodegradation technology of the toxic compounds (organic in nature), two types of biodegradation processes are recognized: That are the aerobic and anaerobic biodegradation [11].…”
Section: Introductionmentioning
confidence: 99%